Case of presymptomatic aceruloplasminemia treated with deferasirox. Issue 12 (23rd January 2014) - Tai, Mayumi; Matsuhashi, Nobuo; Ichii, Osamu; Suzuki, Tomohiro; Ejiri, Yutaka; Kono, Satoshi; Terada, Tatsuhiro; Miyajima, Hiroaki; Harada, Masaru
Abstract : Aceruloplasminemia is an autosomal recessive disease characterized by an abnormal iron metabolism. The absence of ferroxidase activity caused by mutation of ceruloplasmin leads to iron overload in the brain, liver and other organs. We report a 35‐year‐old man who was diagnosed with aceruloplasminemia without neurological manifestation despite the accumulation of iron in the brain and liver. To prevent the development of neurodegenerative disorder related to iron toxicity, iron depletion therapy was performed. Iron chelator deferasirox was effective in reducing serum ferritin level and to prevent the progression of the disease.